its just a matter of combining like terms...
3t + ?h - 5t + ? t + 4h
lets separate our t and h terms...
3t - 5t + ?t......and the answer has to be 1t or just t......lets simplify
-2t + ?t = 1t....so -2 + ? = 1....-2 + 3 = 1...so 3 is our missing t.
lets check....3t - 5t + 3t = 6t - 5t = 1t or just t (correct)
?h + 4h.....and it has to equal 6h
so 4 + what = 6 ? 4 + 2 = 6...so our missing h is 2.
lets check....2h + 4h = 6h (correct)
so ur expression is :
3t + 2h - 5t + 3t + 4h...and when combining like terms, u end up with :
t + 6h